Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1158/1055-9965.epi-16-0167
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Cancer in Asian Americans: A Report of National Mortality Trends by Asian Ethnicity

Abstract: BACKGROUND Asian Americans (AAs) are the fastest growing U.S. population, and when properly distinguished by their ethnic origins, exhibit substantial heterogeneity in socioeconomic status, health behaviors, and health outcomes. Cancer is the second leading cause of death in the US, yet trends and current patterns in the mortality burden of cancer among AA ethnic groups have not been documented. METHODS We report age-adjusted rates, standardized mortality ratios, and modeled trends in cancer-related mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 29 publications
0
93
0
Order By: Relevance
“…40,41 Verifying known clinical trends, Asian patients have the highest topic enrichment values for cancer (0.036), followed by white patients (0.021), other patients (0.016), and black and Hispanic patients (0.015). 42 Black patients have the highest topic enrichment values for kidney problems (0.061), followed by Hispanic patients (0.027), Asian patients (0.022), white patients (0.015), and other patients (0.014). 42 Hispanic patients have the highest topic enrichment values for liver concerns (0.034), followed by other patients (0.024), Asian patients (0.023), white patients (0.019), and black patients (0.014).…”
Section: Results: Enrichment Of Topic Modeled Notesmentioning
confidence: 97%
“…40,41 Verifying known clinical trends, Asian patients have the highest topic enrichment values for cancer (0.036), followed by white patients (0.021), other patients (0.016), and black and Hispanic patients (0.015). 42 Black patients have the highest topic enrichment values for kidney problems (0.061), followed by Hispanic patients (0.027), Asian patients (0.022), white patients (0.015), and other patients (0.014). 42 Hispanic patients have the highest topic enrichment values for liver concerns (0.034), followed by other patients (0.024), Asian patients (0.023), white patients (0.019), and black patients (0.014).…”
Section: Results: Enrichment Of Topic Modeled Notesmentioning
confidence: 97%
“…6 While these data are scant, a small number of studies have examined the trends in the mortality rates among Asian sub-groups with results demonstrating a remarkable heterogeneity in the leading causes of death (e.g., cancer, cardiovascular disease, and stroke) between Asian American subgroups. 5,6 However, aetiology-specific mortality rates in the setting of chronic liver disease among Asian subgroups in the United States on a national level have not been established and have been a limiting factor in improving access to care and addressing health disparities. Several regional studies on state and city levels have attempted to describe the prevalence and patterns of aetiology-based chronic liver disease in Asian subgroups in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…3 As a single group, Asian Americans showed remarkable heterogeneity, reflective of different countries of origin, cultural diversity, educational attainment, socio-economic status, immigration status, lifestyle patterns, insurance coverage, and accessibility of health services. 4,5 Therefore, aggregating Asian Americans into a single group can mask important differences in disease burden and mortality rates. A few studies have described national trends in the health and mortality rates of Asians, [6][7][8] but overall mortality is lower in Asian Americans compared to non-Hispanic whites.…”
mentioning
confidence: 99%
“…Asian Americans (AAs) are highly diverse in terms of health behaviors and outcomes, and the authors of a new report have concluded that this population would benefit from cancer prevention and screening efforts tailored to specific and distinct Asian ethnic subgroups …”
mentioning
confidence: 99%